2018
DOI: 10.1111/weng.12344
|View full text |Cite
|
Sign up to set email alerts
|

The accentedness, comprehensibility, and intelligibility of Asian Englishes

Abstract: This study examines the accentedness, comprehensibility, and intelligibility of speakers of English from China, Hong Kong, Singapore, and the United States (US) by listeners from Hong Kong, Singapore, China, and the US on two speech tasks (read vs. conversation). It also examines the effect of shared background on scores for all listeners as well as the effect of international experience for the Hong Kong and the US listeners. The study found that although accentedness and comprehensibility were positively cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…Several previous studies have highlighted the significance of similarity [6,26], indicating instances where foreign-accented speech might be more intelligible than native speech [3][4]6]. While the present study does partially support this argument (i.e.…”
Section: Effect Of Acoustic Similarity During Foreign-accented Word R...supporting
confidence: 56%
See 2 more Smart Citations
“…Several previous studies have highlighted the significance of similarity [6,26], indicating instances where foreign-accented speech might be more intelligible than native speech [3][4]6]. While the present study does partially support this argument (i.e.…”
Section: Effect Of Acoustic Similarity During Foreign-accented Word R...supporting
confidence: 56%
“…As foreign accents could be viewed as a barrier to international communication, extensive research has focused on understanding whether and how foreign accents affect listener intelligibility. Most studies define intelligibility as the extent to which a speaker's message is actually understood by a listener, often measured by asking listeners to transcribe what they hear and calculating the intelligibility score based on the total number of words transcribed correctly [1][2][3]. Prior research has shown that foreign-accented speech is often less intelligible to native speakers of the target language (e.g., Spanish-accented English perceived by native (L1) English speakers) [1,[3][4].…”
Section: Foreign Accent and Intelligibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…According to the findings, NNLs received higher intelligibility scores than NLs; however, the differences were rather small without statistical significance. Similarly, in several other studies, NNTs were found to be more intelligible to NNLs with a shared L1, yet the NNLs did not outperform NLs (Han et al, 2011;Hansen Edwards et al, 2018;Jułkowska & Cebrian, 2015;Lee et al, 2005). Despite these research efforts in various contexts, there is a clear research gap in terms of ISIB studies conducted with Turkish talkers and listeners.…”
Section: Literature Reviewmentioning
confidence: 54%
“…For LC, "1" meant "very easy to understand" and "9" meant "very hard to understand" (Munro and Derwing, 1995a, and adapted by many studies). For AP, "1" meant "no non-native accent at all" and "9" meant "very heavy foreign accent" (Hansen Edwards et al, 2018). For AA1, "1" meant "the accent was very pleasant to listen to" and "9" meant "the accent was very annoying and irritating," respectively (Szpyra-Kozlowska, 2014).…”
Section: Preparation Of Online Testingmentioning
confidence: 99%